The Mechanism of Legal Translation in Legislative Texts - Mohammed, Marwan Kazem; Farhan, Mohammed Dera; Mohammed, Awham Rasheed (Al-Adab Journal, 2022)
The concepts of globalization and one village used to express the world in which we live today are based on openness to others in all fields. Language is the most widely used tool that man relies on to achieve that openness through expressing his ideas and communicating with others. The need of the age for translation has widely emerged because of its great role in achieving that expression or communication. Translation played the most prominent role in all fields to achieve that openness and communication with others. The importance of legal translation has increased in our world today because of its great importance in the transmission of laws, legislation and official documents that require high skill and great accuracy in translating them, not only for linguists but also for the men of law to achieve the basic objectives of that communication and openness. Legal translation requires great professionalism and accurate knowledge of the field from which we are translating, as the difference in translation or its inaccuracy has unimaginable consequences. Marriage contracts are considered one of the noblest human contracts concluded between two parties, and the Holy Qur’an called it a “thick pact” because of its importance and sacred status. Given the importance of this document, this study presents one of the problems that lead to the literal translation that may be adopted by the Jannat Iraq College if there are no specializations and specialized advisory offices for this purpose, whether for law students or local courts and individuals with contracts who migrate or travel outside the country by relying on this type of translation. Consequently, they incur financial losses in addition to the difficulty of travel and immigration, and waste of time and effort. This study aims to shed light on the translation of legal contracts such as marriage contracts, to show the common errors in them, to give enough space to translate contracts in the academic curricula so that law students can know the correct and appropriate translation and its difference between countries, improve the translation reality and provide translators with high qualifications in legal translation. And then develop possible solutions and proposals that would raise the level of performance of Iraqi Jannat Civil College, in line with its mission, goals and vision.